A questão de Timor-Leste no jornal público: a voz do Bartoon - Calgaro, Gisele (2006)
This research work is primarily based on the analysis of the Bartoons a series of comic strips made by the Portuguese cartoonist Luís Afonso. Special attention is drawn to the voice that emerges from the enunciation of its discourse and how it has contributed to make the Portuguese reader reflect upon the independence of East Timor from Indonesia. For the purpose of this study, seven Bartoons published between the 6th and the 24th of September 1999, in the Espaço Público section in the Portuguese newspaper Público, were chosen at random. Since the Bartoons re-create, intertextually, the social political moment prior to the arrival of ONU s Peace Force and the conquest of East Timor independence, a brief historical retrospective and some contextualization of the country s situation are presented. In order to provide a detailed discussion, it was necessary to refer to the constituent elements of the comic strip genre. Thus, McCloud (2005) and Eisner (2001; 2005) were taken into account. Considering the general aspects involving the construction of the ethos in the Discourse Analysis, Maingueneau s theory (1997; 2005) revealed as the most appropriate one. At last, this analysis tried to reveal the satirical voice used in the making of the strips wisely associated with the discoursive denunciation presented in the drawings. Moreover, by using irony, the analysis empathizes with the East Timorese s suffering and disqualifies their oppressors, trying to touch the reader and persuade him/her to feel indignant and think over the subject.